Reality of cross-nursing in a Philanthropic Maternity Hospital in Aracaju, Sergipe (Research, Society and Development, 2021)
Objective. This study aims to assess the knowlegde of the women about the practice of crossfeeding. Methods. Observational, prospective and analytical study carried out in a Philanthropic Hospital and Maternity in Aracaju SE, from August to November 2021. The population used in the research consisted of mothers referred to rooming-in and specialized outpatient clinic of the Hospital and Maternity Santa Isabel, being applied a questionnaire by the researchers. Results. The prevalence of cross-breastfeeding was 49.16%, considering that 31.11% (n=42) of the mothers breastfed one or more children other than their child and 18.05% (n=24) had their child breastfed for one or more nursing mothers. 62.22% of them did not know what cross-breastfeeding was. 52, 59% were aged between 21 and 30 years. As for the race, most were configured as non-white. 16.30% lived in rural areas. Less than half, 40.60%, declared themselves to be married or in a stable relationship. 74.81%, lived with less than one salary at one minimum wage per month and also did not have a formal paid job, 87.41%. 65.19% of them received Bolsa Família aid. Only 5.19% had completed or incomplete higher education. When the variables were compared, two P-values were noted with significance levels, p=0.002 and p=0.031, corresponding to whether mothers knew the risk of cross-breastfeeding or whether they had been breastfed by a woman other than the mother, respectively. Conclusion. Despite being prohibited in Brazil, crossfeeding is still recurrent, in high percentages and there is a lack of information on the subject.